Utilisation of Cow Faeces as a Base Material to Making Bokashi Fertiliser to Increase Farmers Income in Balai Hamlet, Taram Village, Harau District - Mukhlis, Mukhlis; Fitrianti, Siska; Wisra, Raeza Firsta; Hendriani, Riva; Sari, Nila (Unram Journal of Community Service, 2024)
The application of technology in agriculture aims to increase food production through the substitution of traditional farming systems with modern farming systems by utilising more advanced technology. This has an impact on the use of chemical fertilisers and pesticides, which can cause environmental damage and ultimately reduce agricultural productivity. Processing cow dung into organic fertiliser for crops is an applied technology in the framework of implementing zero waste farming technology. One of the benefits that can be obtained is increased income by reducing the cost of artificial fertiliser needs. Cow faeces as cattle farming waste has not been optimally utilised. Cow faeces are usually piled up by farmers behind or near the cowshed, causing a strong smell (air pollution). The results of the activity of making cow feces bokashi organic fertiliser are very beneficial for farmers as a substitute for inorganic fertiliser; The creation of clean cowshed conditions, and environmentally friendly rice fields.